Digest - Herfarth, Christian; Lehnert, Thomas (The British journal of surgery, 1995)
For this quarter's digest Professor Christian Herfarth and Dr Thomas Lehnert have selected the best from the July to September 1994 issues of Der Chirurg. A digest of the BJS for the same period, written by Professor John Farndon, appears in the German Journal.
Elektronische Reproduktion der Druck-Ausgabe 2. Dezember 2005
Gesehen am 08.09.2025